Nasal Foreign bodies: Review of 195 patients - Aws Adel AL-HUSSONA; Saddam Sahib ATSHAN (University of Thi-Qar Journal of Science, 2019)
Objectives: To assess the characteristics of 195 cases with nasal foreign bodies regarding the sex , age , types , site and complain at presentation.Materials and Methods : One hundred ninety five patients with nasal foreign bodies , their age range of 1-12 years old visiting the private clinic from March 2010 – June 2015 retrospectively analyzed.Results : The nasal foreign bodies mostly presented with males , the most common age group from 1-6 years and the most common foreign bodies were beads and plastic toys.Conclusions : Nasal foreign bodies one of the most common otolaryngological emergencies in pediatric practice , although it is not life threatening , it still need special care to prevent complications.